Long Lamai Community Ict4d E-Commerce System Modelling: An Agent Oriented Role-Based Approach - Cheah, Wai Shiang; Alfian, Abdul Halin; Lu, Marlene; Chee, Gary Whye (City University of Hong Kong, 2016)
This paper presents the post-mortem report upon completion of the Long Lamai e-commerce development project. Some weaknesses with regards to the current software modelling approach are identified and an alternative role-based approach is proposed. We argue that the existing software modelling technique is not suitable for modelling, making it difficult to establish a good contract between stakeholders causing delays in the project delivery. The role-based approach is able to explicitly highlight the responsibilities among stakeholders, while also forming the contract agreement among them leading towards sustainable ICT4D.